THE UTILIZATION OF DIGITAL ASSESSMENT FOR A BETTER LEARNING EXPERIENCES (Penggunaan Penilaian Digital untuk Pengalaman Belajar yang Lebih Baik) - Nukmatus Syahria (Sirok Bastra, 2019)
Technology is now becoming an unavoidable part of Indonesian students’ life. The application of digital tools have facilitated the students to expand their knowledge and develop their learning. At the same time, it helps to plant learning autonomy toward the students. This paper aimed to explore the teachers’ experiences in applying the digital assessment by using in- depth interview and classroom observation. The teachers can gain a lot of advantages by applying the digital assessment in their teaching and learning activities. It saves a lot of teachers’ time, it breaks the barriers between teachers and students in terms of meeting time and at the same time it also helps to reduce students’ anxiety during the assessment. However, during the application of the digital assessment there were several difficulties faced by the teachers, namely the internet connection, the misconception among the students because the students did not comprehend well regarding the teachers’ feedback as well as there may be a possibility for the students to cheat during the assessment since they can do it anywhere not only in the campus. The teachers’ mastery in technology indirectly can also help the development of Indonesia’s education system. Teknologi kini menjadi bagian tak terpisahkan dari kehidupan siswa Indonesia. Penerapan perangkat digital telah memfasilitasi siswa untuk memperluas pengetahuan dan mengembangkan cara belajar mereka. Pada saat yang bersamaan,  perangkat digital juga membantu menanamkan otonomi belajar kepada siswa. Artikel ini bertujuan untuk mengeksplorasi pengalaman para guru dalam menerapkan penilaian secara digital dengan menggunakan wawancara secara intensif dan observasi kelas. Para guru dapat memperoleh banyak keuntungan dengan menerapkan penilaian secara digital dalam kegiatan belajar mengajar mereka. Penilaian dengan cara seperti ini menghemat banyak waktu guru, menjembatani jarak antara guru dan siswa dalam hal waktu pertemuan dan pada saat yang sama juga membantu mengurangi kecemasan siswa selama penilaian. Namun, dalam penerapannya, terdapat beberapa kesulitan yang dihadapi oleh para guru, yaitu koneksi internet, kesalahpahaman di antara siswa karena siswa tidak memahami dengan baik tentang umpan balik guru dan terdapat kemungkinan siswa menyontek selama ujian karena mereka dapat melakukannya di mana saja, tidak hanya di area kampus. Penguasaan guru tentang teknologi secara tidak langsung juga dapat membantu pengembangan sistem pendidikan di Indonesia.